The Impact of English Cartoon Movies on Vocabulary Acquisition Among EFL Learners - Fitra Ramadani; M Arbain; Hartatya Novika (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
This study investigates the impact of English cartoon movies on vocabulary acquisition among EFL learners, with a focus on both receptive and productive vocabulary knowledge. It also explores retention and the influence of mediating variables such as proficiency level and captioning. Employing a one-group pretest-posttest design, the study involved 25 purposively selected junior high school EFL students with limited English exposure outside the classroom. Participants first completed a vocabulary pretest, then received treatment through guided exposure to an English cartoon movie (e.g., Dora the Explorer), and finally took a posttest. The results revealed a significant improvement in vocabulary scores, with the mean increasing from 75.16 (pretest) to 87.92 (posttest), yielding a mean gain of 12.76 points. Statistical analysis using a paired sample t-test produced a t-value of 5.21 (p < 0.05), indicating that the difference was statistically significant. These findings support Dual Coding Theory and Constructivist learning principles, emphasizing the role of multimedia input in enhancing vocabulary learning. The use of cartoon-based audiovisual media proved effective across varying proficiency levels, narrowing learning gaps and promoting contextual vocabulary retention.